Incomplete seating of modular dual mobility - Stallone, Stefano; Pungetti, Camilla; Melucci, Giuseppe; Castiello, Emanuela; Pugliese, Mattia; Pizzo, Alex; Tigani, Domenico (Lo Scalpello - Journal, 2024)
Objective. Instability is considered a leading cause of early revision in total hip arthroplasty. Dual mobility cup (DMC) has shown to be a good solution for this problem. However, using DMC there is the potential complication of malseating of the liner. The study aims to determine the incidence of DMC malseating in a large volume hospital where different modular constructs are used, and if there is a significant difference in the incidence between the different constructs used. Methods. In this retrospective study, we included patients admitted at single institution from January 2016 to March 2020. One-hundred-and-one patients were enrolled. Fifty-seven patients were male, the mean age was 61 years, and the mean body mass index was 25.9 kg/m2. Results. Three patients had radiographic evidence of liner malseating. In one patient, the radiological divergence disappeared at one-year follow-up. One patient showed an unfavorable evolution with a progressive increase of the divergence of the shell line associated with a painful noise. He eventually underwent revision surgery. Conclusions. In high-risk patients, DMC component provided a low risk of dislocation and good overall survival.